Aktuelle Bestandsabschätzungen wirtschaftlich wichtiger Grundfischarten im Nordostatlantik - Schöne, Rüdiger (1995)
Assessments on stocks of cod, haddock, saithe, redfish and Greenland halibut were carried out by the "Arctic Fisheries Working Group" in August 1995. The most important results are given in this report.